Lecithoceridae (Lepidoptera: Gelechioidea) of New Guinea, Part IV: Genus Pectinimura Park with descriptions of four new species and four new combinations - Park, Kyu-Tek (Zootaxa, 2011)
As the 4 th part in a series of papers on the family Lecithoceridae (Lepidoptera, Gelechioidea) of New Guinea, the genus Pectinimura Park is reviewed, describing P. singularis sp. nov., P. areola sp. nov., P. brahmanica sp. nov., and P. gilvicostata sp. nov. Four previously known species belonging to Lecithocera are transferred to Pectinimura: P. baryoma (Diakonoff), comb. nov., P. liberalis (Diakonoff), comb. nov., P. lutescens (Diakonoff), comb. nov., and P. rhabdostoma (Diakonoff), comb. nov. Adults, heads, labial palpi, and the male genitaia are illustrated. A worldwide catalogue of the genus is provided.